2014
DOI: 10.1007/s00439-014-1521-6
|View full text |Cite
|
Sign up to set email alerts
|

CDH13 promoter SNPs with pleiotropic effect on cardiometabolic parameters represent methylation QTLs

Abstract: CDH13 encodes T-cadherin, a receptor for high molecular weight (HMW) adiponectin and low-density lipoprotein, promoting proliferation and migration of endothelial cells. Genome-wide association studies have mapped multiple variants in CDH13 associated with cardiometabolic traits (CMT) with variable effects across studies. We hypothesized that this heterogeneity might reflect interplay with DNA methylation within the region. Resequencing and EpiTYPER™ assay were applied for the HYPertension in ESTonia/Coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…One of the mechanism through which CDH13 SNPs may affect the expression of the CDH13 gene was reported by Putku et al 28) , who showed that some of SNPs around the CpG island within the regulatory region of the CDH13 gene affect the methylation levels of the gene region. Adiponectin-inducing alleles of SNPs (rs8060301 and rs12444338) were related to hypermethylation within the CpG island, which would reduce the expression of CDH13.…”
Section: Coimentioning
confidence: 99%
“…One of the mechanism through which CDH13 SNPs may affect the expression of the CDH13 gene was reported by Putku et al 28) , who showed that some of SNPs around the CpG island within the regulatory region of the CDH13 gene affect the methylation levels of the gene region. Adiponectin-inducing alleles of SNPs (rs8060301 and rs12444338) were related to hypermethylation within the CpG island, which would reduce the expression of CDH13.…”
Section: Coimentioning
confidence: 99%
“…Four common variants (rs12443878 C/A, rs12444338 G/T, rs62040565 C/T, and rs8060301 A/T) exhibited effects on methylation levels of up to 3 CpG sites located 19-167,744 bp from the respective SNPs. SNP rs8060301 was also associated with highmolecular-weight adiponectin levels [184]. Rs8060301 is in LD with the previously described SNP rs4783244.…”
Section: Epigeneticsmentioning
confidence: 62%
“…A recent study by Putku et al showed that the CDH13 promoter harbors methylation quantitative trait loci (meQTLs) associated with cardiometabolic traits [184]. Four common variants (rs12443878 C/A, rs12444338 G/T, rs62040565 C/T, and rs8060301 A/T) exhibited effects on methylation levels of up to 3 CpG sites located 19-167,744 bp from the respective SNPs.…”
Section: Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous reports of SNPs affecting the hypermethylation of proximal and trans-gene CpG islands, [2][3][4][5][6] Table 3. Allele frequencies for the non-hg19 SNP alleles that occur most frequently in the indicated data sets and that create or eliminate CpG's.…”
Section: Discussionmentioning
confidence: 99%